ChemInform Abstract: Synthesis, Structure, and Properties of Turbostratically Disordered (PbSe)1.18(TiSe2)2. Issue 35 (8th August 2013) - Moore, Daniel B.; Beekman, Matt; Disch, Sabrina; Zschack, Paul; Haeusler, Ines; Neumann, Wolfgang; Johnson, David C.
Abstract The title compound is prepared by annealing (350 °C, N2) a system of 28 repetitions of sputtered layer sequences of Ti‐Se‐Ti‐Se‐Pb‐Se.